PENGARUH STRES DAN TIM KERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PEGAWAI PADA BALAI DIKLAT KEAGAMAAN SURABAYA - Ernawati, Novita (MAP (Jurnal Manajemen dan Administrasi Publik), 2025)
This study aims to analyze the influence of work stress and work team on employee performance with job satisfaction as an intervening variable at the Surabaya Religious Education and Training Center. This study uses a quantitative approach with a survey method. The population of this study is all employees of the Surabaya Religious Education and Training Center which totals 72 people, with this study using a total sampling technique, so that all members of the population are made respondents. The results of the study show that work stress has a negative and significant influence on job satisfaction and employee performance. On the other hand, the work team has a significant positive influence on job satisfaction and on employee performance. In addition, work stress affects performance indirectly through job satisfaction, while work teams have a positive effect on performance through job satisfaction. This confirms that job satisfaction has an important role as a mediating variable that can strengthen the relationship between organizational factors and employee performance.